TINJAUN PUSTAKA; PERILAKU PENYIMPANG PADA REMAJA - Ayu Lestari (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
Deviant behavior committed by teenagers generally occurs at the age of junior high school and high school. At school age, adolescents are vulnerable to influence and the psyche is still very unstable. There are many positive and negative influences that teenagers, Indonesia among teenagers, can accept is often encountered regarding social problems that arise in various forms and are considered quite worrying. This study aims to see the picture of deviant behavior of adolescents, the existence of family conditions such as permissive parenting or family conflicts, the role of which is very important. In terms of environmental factors such as a lack of support for the community and limited access to education and positive activities can exacerbate deviant behavior. This study uses the literature review study method. Keyword: Devianism in Adolescents